Rational expectations and the puzzling no-effect of the minimum wage - Sara Pinoli (Uppsala University, Department of Economics, 2010)
This paper argues that expectations are an important element that need to be included into the analysis of the effects of the minimum wage on employment. We show in a standard matching model that the observed employment effect is higher the lower is the likelihood associated with the minimum wage variation. On the other side, there is a significant anticipation effect, ignored in the literature. This property is able to explain the controversial results found in the empirical studies. When the policy is anticipated, the effect at the time of the actual variation is small and potentially hard to identify. The model is tested on Spanish data, taking advantage of the unexpected change in the minimum wage following the election of Zapatero in 2004.
urn:nbn:se:uu:diva-126603
Keywords: D21; J23; J38; 330; Minimum wage; Expectations; Heterogeneous matches; Mindestlohn; Wirkungsanalyse; Rationale Erwartung; Beschäftigungseffekt; Schätzung; Spanien